2020
DOI: 10.4193/rhin19.292
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal endonasal perception – an outcome predictor for septoplasty

Abstract: Background:No adequate test exists to predict outcome after septoplasty. Despite adequate surgery, patients still might experience nasal breathing impairment. The aim of this study was to determine if pre-operative trigeminal sensitivity can predict satisfaction after septoplasty. Methods:Single centre prospective cohort study in tertiary referral centre with follow-up time of 6 weeks postoperatively.Patients scheduled for septoplasty or septorhinoplasty with turbinoplasty were consecutively selected the day b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In other words, our results suggest that the trigeminal system, which is known to be involved in airflow perception (17) , plays a role in the pathogenesis of CNO. Our results further support previous observations that underline the importance of identifying patients with poor intranasal trigeminal sensitivity prior to nasal surgery (8,24) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, our results suggest that the trigeminal system, which is known to be involved in airflow perception (17) , plays a role in the pathogenesis of CNO. Our results further support previous observations that underline the importance of identifying patients with poor intranasal trigeminal sensitivity prior to nasal surgery (8,24) .…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that an altered perception of nasal patency in CNO may be caused by altered afferent neural pathways responsible for airflow perception (4) . Low intranasal trigeminal function seems to predict poor postoperative satisfaction after septal surgery (8) , underling the implication of airflow perception in nasal obstruction.…”
Section: Introductionmentioning
confidence: 96%
“…The missing gap may be the lack of information about trigeminal function. Ultimately, an improvement of more than 3 VAS points after septoplasty can be predicted by a lateralisation test score of >31.5 (88% sensitivity) [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems more practical to assess intranasal trigeminal function only in specific rhinological conditions at clinical practice. For example, it can be initially used in patients for whom there is evidence of potential low trigeminal sensitivity such as patients scheduled for septoplasty, patients with empty nose syndrome, patients with nasal obstruction without specific clinical findings, patients suspected of having olfactory dysfunction [6,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Migneault-Bouchard et al (58) showed that trigeminal function appears to be more informative than mechanical resistance in patients with treatment refractory nasal obstruction, and Bischoff et al (59) published data suggesting that intranasal trigeminal function predicts satisfaction after septoplasty.…”
Section: Trpm8 Importance For Intranasal Trigeminal Functionmentioning
confidence: 99%